Does Whipping Tournament Incentives Spur CSR Performance? An Empirical Evidence From Chinese Sub-national Institutional Contingencies - Khan, Muhammad Kaleem; Ali, Shahid; Zahid, R. M. Ammar; Huo, Chunhui; Nazir, Mian Sajid (Frontiers in Psychology, 2022)
The current study investigates whether tournament incentives motivate chief executive officer(s) (CEOs) to be socially responsible. Furthermore, it explores the role of sub-national institutional contingencies [i.e., state-owned enterprises (SOE) vs. non-SOEs, foreign-owned entities (FOE) vs. non-FOEs, cross-listed vs. non-cross-listed, developed region] in CEO tournament incentives and the corporate social responsibility performance (CSRP) relationship. Data were collected from all A-shared companies listed in the stock exchanges of China from 2014 to 2019. The study uses the baseline methodology of ordinary least squares (OLS) and cluster OLS regression. Moreover, firm-fixed effects regression, two-stage least squares regression, and propensity score matching deal with the endogeneity problem and check the robustness of the results. The results provide reliable evidence that tournament incentives motivate CEOs to be more socially responsible. On the other hand, sub-national institutional contingencies positively affect the association between CEO tournament incentives and CSRP. The findings have important implications for companies and regulators who wish to enhance CSP by providing incentives to top managers.